Education on Factors Influencing Couple of Reproductive Age in Choosing Implants Contraception At Gonting Malaha Health Center - Purba, Anita Sri Gandaria (JURNAL PENGMAS KESTRA (JPK), 2023)
The Family Planning (KB) program has a role in reducing the population's birth rate so that fertility and birth rates can be controlled. Regulating the spacing of pregnancies, birth spacing, and determining the number of children in a family are expected to reduce population growth. The family planning program was initiated by the government to reduce the population explosion. Many factors influence couples of childbearing age in choosing the right contraception. For example, the weight factor changes due to use, and experiencing allergies. Some of the mothers also set the time of birth. Implants are very effective but still quite low. Where the implant can be removed at any time, is not dangerous, and does not affect sexual activity. Service activities are carried out through lectures, discussions, and education methods. The number of participants in this PkM activity was 10 health workers at the Gonting Malaha Health Center. The activity begins with the provision of pretest and posttest which are presented in written form and are of course related to the material to be taught. The results of PkM activities through education show that it is the low knowledge factor that causes couples not to choose implant contraception, namely 60%. Knowledge, education, and parity factors influence couples in choosing implant contraception with a p-value less than 0.05. PkM participant post-test scores always increased after being given education with the highest increase of 25% and the lowest increase of 20%. The average increase in knowledge of all PkM participants increased to 23% when compared to the beginning. So it can be stated that this PKM activity has succeeded in educating PKM participants in knowing the factors of partners in choosing implant contraception.